スピッツベルゲン ノ Ny-Alesund チイキ ニ オケル ショクセイ ノ ショクブツ シャカイガク テキ ケンキュウ - 小林, 圭介; コバヤシ, ケイスケ; Kobayashi, Keisuke (1994)
P(論文) スピッツベルゲンのNy-Ålesund地域において, 維管束植物と蘚苔地衣類から構成された植生を植物社会学的に解明した。特に, これまで優占種に主体をおいた植生単位の抽出がなされていたが, 本研究では種の結びつきと適合度に基づき, さらに表操作ではコンピューターを使用することによって, 興味ある植生単位を識別することができた。識別した植生単位は, 1. Saxifragetum cernuae KOBAYASHI 1994 prov. : a. Subass. of typicum, b. Subass. of Orthothecium chryseum, c. Subass. of Leptobryum pyriforme, d. Subass. of Cetraria delisei. 2. Dryadetum minoris HADAC 1946em. KOBAYASHI 1994 : a. Subass. of Racomitrium lanuginosum, b. Subass. of Lecanora epibryon. 3. Xanthoria elegans communityの2群集と6亜群集, および1群落である。これら植生単位について, 種組成, 生態, 分布などの記載を行った。さらに, これら植生単位については, 類似度の指数から相互関係を分析して, 植生単位と種組成および立地の関係を明らかにした。 This paper was undertaken to classify and describe the vegetation of the Ny-Ålesund area in Spitsbergen using the method of the Z-M school of phytosociology. The investigations were carried out at 55 stands which were located in an area ranging from the coast to the mountain regions in and around Ny-Ålesund. The vegetation investigated was classified according to the fidelity of species and the species combination. The term "association" was adopted as the fundamental unit of the vegetation with the exception of the provisional vegetation unit treated as the community. Moreover, associations were subdivided into subassociations according to the scale of the floristic variation. On the basis of the data obtained from 55 stands in the Ny-Ålesund area, the following vegetation units were classified : 1. Saxifragetum cernuae KOBAYASHI 1994 prov. : a. Subass. of typicum, b. Subass. of Orthothecium chryseum, c. Subass. of Leptobryum pyriforme, d. Subass. of Cetraria delisei. 2. Dryadetum minoris HADAC 1946em. KOBAYASHI 1994 : a. Subass. of Racomitrium lanuginosum, b. Subass. of Lecanora epibryon. 3. Xanthoria elegans community. They belong to some higher units left to be investigated in the future. Each of the vegetation units classified is described with an association table showing the floristic composition and data about growing habitats. Their distribution is made clear by showing the actual ...